Baseline associations between postmenopausal hormone therapy and inflammatory, haemostatic, and lipid biomarkers of coronary heart disease - Langer, Robert D.; Pradhan, Aruna D.; Lewis, Cora E.; Manson, JoAnn E.; Rossouw, Jacques E.; Hendrix, Susan L.; LaCroix, Andrea Z.; Ridker, Paul M. (Thrombosis and Haemostasis, 2005)
Clinical trials of postmenopausal hormone therapy (PHT) have found an early increase in cardiovascular events, and have not demonstrated the reduction in coronary heart disease (CHD) predicted from changes in conventional risk factors or found in observational studies, suggesting that PHT may increase coronary risk through other pathways. We compared baseline levels of C-reactive protein (CRP), interleukin-6 (IL-6), sICAM-1, tissue plasminogen activator antigen (tPA-antigen), D-dimer, homocysteine, triglycerides, total-, HDL- and LDL- cholesterol in 304 cases with incident CHD and 304 controls, according to self-reported use of PHT. Subjects were selected from the 75,343 participants in the WHI Observational Study without baseline cardiovascular disease or cancer. PHT was associated with higher CRP, HDL and triglycerides, and lower tPA-antigen and homo-cysteine. CRP was highest in users of unopposed conjugated equine estrogen. Levels of IL-6, sICAM-1, D-dimer and total cholesterol did not differ between PHT users and non-users. Trans-dermal estrogen users had low levels of D-dimer and CRP. Among users of estrogen plus progestin (EP), CRP, IL-6, tPA-antigen, D-dimer, total cholesterol and triglycerides were higher in women with incident coronary events than controls. Estrogen alone (E) controls shared only the tPA-antigen association, but had higher HDL and lower LDL than E cases. In non-users CRP, tPA-antigen and D-dimer were associated with incident CHD. In summary, risk markers differed by PHT category. Some associations differed between women with and without incident CHD, especially for EP, where inflammatory and thrombotic markers were higher in cases. These associations remain speculative pending confirmation in randomized trials.
Keywords: Postmenopausal hormone therapy; estrogens; coronary heart disease; inflammatory factors; haemostatic factors